Soft computing applications and techniques in healthcare - Mishra, Ashish (Ashish Kumar); Suseendran, G.; Phung, Trung-Nghia (Boca Raton : CRC Press, 2020)
"This book provides insights into contemporary issues and challenges in soft computing applications and techniques in healthcare"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Technological innovations; Medical informatics; Medical technology; TECHNOLOGY / Operations Research; COMPUTERS / Computer Science